ANTICORPS - VEITONMÄKI, Niina; ELLMARK, Peter; NORLEN, Per (2019)
The present invention relates to combination therapies for treating a solid tumour in a subject. The combination therapies comprise (a) an antibody, or antigen-binding portion thereof, that specifically binds to CD40, and (b) a further immunotherapeutic agent with efficacy in the treatment of cancer, which agent is not an anti-CD40 antibody or antigen-binding fragment thereof. The invention also relates to a kits and methods of using such therapies.